DESIGN AND ANALYSIS OF FORMULA CAR CHASSIS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Every year two competitions are held by Society of Automotive Engineers in India. The first being, FORMULA BHARAT and the second being SAE Supra. These two competitions primarily are based on design, safety and performance of the car that are built by various universities all over from India